Applying Integrated Computer Assisted Media (ICAM) in Teaching Vocabulary - Opik Dwi Indah (Universitas Cokroaminoto Palopo, 2015)
The objective of this research was to find out whether the use of integrated computer assisted media (ICAM) is effective to improve the vocabulary achievement of the second semester students of Cokroaminoto Palopo University. The population of this research was the second semester students of English department of Cokroaminoto Palopo University in academic year 2013/2014. The samples of this research were 60 students and they were placed into two groups: experimental and control group where each group consisted of 30 students. This research used cluster random sampling technique. The research data was collected by applying vocabulary test and it was analyzed by using descriptive and inferential statistics. The result of this research was integrated computer assisted media (ICAM) can improve vocabulary achievement of the students of English department of Cokroaminoto Palopo University. It can be concluded that the use of ICAM in the teaching vocabulary is effective to be implemented in improving the students’ vocabulary achievement.